Assessment of EEG-based functional connectivity in response to haptic delay - Alsuradi, Haneen; Park, Wanjoo; Eid, Mohamad (Frontiers in Neuroscience, 2022)
Haptic technologies enable users to physically interact with remote or virtual environments by applying force, vibration, or motions via haptic interfaces. However, the delivery of timely haptic feedback remains a challenge due to the stringent computation and communication requirements associated with haptic data transfer. Haptic delay disrupts the realism of the user experience and interferes with the quality of interaction. Research efforts have been devoted to study the neural correlates of delayed sensory stimulation to better understand and thus mitigate the impact of delay. However, little is known about the functional neural networks that process haptic delay. This paper investigates the underlying neural networks associated with processing haptic delay in passive and active haptic interactions. Nineteen participants completed a visuo-haptic task using a computer screen and a haptic device while electroencephalography (EEG) data are being recorded. A combined approach based on phase locking value (PLV) functional connectivity and graph theory was used. To assay the effects of haptic delay on functional connectivity, we evaluate a global connectivity property through small worldness index and a local connectivity property through nodal strength index. Results suggest that the brain exhibits significantly different network characteristics when a haptic delay is introduced. Haptic delay caused an increased manifestation of the small worldness index in the delta and theta bands as well as an increased nodal strength index at the middle central region. Inter-regional connectivity analysis showed that the middle central region was significantly connected to the parietal and occipital regions as a result of haptic delay. These results are expected to index the detection of conflicting visuo-haptic information at the middle central region and their respective resolution/integration at the parietal and occipital regions.